The effect of NPK fertilization and the number of plants on the yield of maize hybrids with different genetic base in half-industrial experiment - Kovács, Péter; Sárvári, Mihály (Acta Agraria Debreceniensis, 2016)
In our research we examined the effect of the hybrid, the nutrient supply, the number of plants and the abiotic factors (temperature, amount of precipitation) on the yield, crop quality and yield stability of maize. We devoted special attention to the natural nutrient utilization ability and fertilizer reaction of maize.The experiment took place in Hajdúszoboszló on chernozem soil, on a nearly 8 ha field. The size of one plot was 206 m2, this it was a halfindustrial experiment. We tested six hybrids with different genetic characteristics and growing seasons. I analysed the correlation between the nutrient supply and the yield of maize hybrids with control treatment (treatment without fertilization) and with N 80, P2O5 60, K2O 70 kg ha-1 and N 160, P2O5 120, K2O 140 kg ha-1 fertilizer treatments. Yield increasing effect of the fertilizer also depended on the number of plants per hectare at a great extent. The number of plants of the six tested hybrids was 60, 70, and 80 thousand plants/ha.In Hajdúszoboszló, in 2015 the amount of rainfall from January to October was 340.3 mm, which was less than the average of 30 years by 105.5 mm. This year was not only draughty but it was also extremely hot, as the average temperature was higher by 1.7 °C than the average of 30 years. In the critical months of the growing season the distribution of precipitation was unfavourable for maize: in June the amount of rainfall was less by 31mm and in July by 42 mm than the average of many years.Unfavourable effects of the weather of year 2015 were reflected also by our experimental data. The yield of hybrids without fertilization changed between 5.28–7.13 t ha-1 depending on the number of plants.It can be associated also with the unfavourable crop year that the yield of the six tested hybrids is 6.33 t ha-1 in the average of the stand density of 60, 70 and 80 thousand plants per hectare without fertilization, while it is 7.14 t ha-1 with N80+PK fertilizer treatment. That increase in the yield is only 0.81 t ha-1, but it is significant. Due to the especially draughty weather the yield increasing effect of fertilizers was moderate. In the average of the hybrids and the number of plants, increasing the N80+PK treatment to N160+PK, the yield did not increase but decreased, which is explicable by the water scarcity in the period of flowering, fertilization and grain filling.The agroecological optimum of fertilization was N 80, P2O5 60 and K2O 70 kg ha-1. Due to the intense water scarcity, increased fertilization caused decrease in the yield. As for the number of plants, 70 000 plants ha-1 proved to be the optimum, and the further increase of the number of plants caused decrease in the yield.